The Causes of Anarchy in Samarra and its Consequences for the Abbasid Caliphate - Rakhmanova Odinakhon Ravshanbekovna (Scientific Trends, 2025)
Anarchy in Samarra (861-870) - a period of acute political instability in the Abbasid Caliphate, caused by the conflict between factions of the Turkic guard and the weakening of central authority. The article systematically analyzes the causes of the Samarra crisis - from the institutional changes associated with al-Mu'tasim's establishment of the new capital of Samarra and the formation of a professional army of ghulams, to the political intrigues at al-Mutawakkil's court. It demonstrates how the concentration of power in the hands of Turkic military commanders led to a series of palace coups from 861 to 870 and reduced the caliphs to puppets under their control. Military, political, and social factors, including the role of the conflict between the new Turkic elite and the old Arab nobility, are examined separately. The consequences of the anarchy in Samarra for the Abbasid Caliphate were revealed: the actual disintegration of a unified empire, the loss of control by the central government over provinces, and the transition to a decentralized system of local dynasties. In conclusion, the impact of the Samarra events on the subsequent decline of the Caliphate is summarized, and the author's conclusions regarding the patterns of this crisis situation are presented.
Keywords: Samarra, Abbasid Caliphate, Turkish Guard, al-Mutawakkil, anarchy, ghulams, palace coups, decentralization.